Treatment of Membranous Nephropathy in Chinese Patients: Comparison of Rituximab and Intravenous Cyclophosphamide with Steroids - Xiaofan Hu; Hong Ren; Jing Xu; Chenni Gao; Yifan Wu; Yan Ouyang; Li Lin; Xiao Li; Na Liu; Weiming Wang; Jingyuan Xie; Nan Chen (Karger Publishers, 2024)
Introduction: Previous studies have shown that rituximab (RTX) and cyclic oral corticosteroid-cyclophosphamide (CTX) regimens have similar effects on Primary Membranous Nephropathy. However, no studies have compared RTX with an intravenous CTX regimen, which is more commonly used in China and requires fewer cumulative CTX doses. Methods: We prospectively assigned 141 PMN patients with baseline proteinuria ≥ 4 g/24 h, serum albumin < 30 g/L, and eGFR ≥ 30 mL/min × 1.73 m2 despite at least 3 months of treatment with ACEI and/or ARB to the RTX group (375 mg/m2 per injection per week × 4 injections) or to the CTX group (prednisone 0.8 mg/kg/d and intravenous CTX 500 mg/m2 per month until the total dose reached 6-8 g). The primary endpoint was defined as a combination of partial remission or complete remission at 12 months. Results: By the end of 12 months, 43 of 70 patients (61.43%) in the RTX group and 54 of 71 patients (76.06%) in the CTX group reached the primary endpoint(P=0.06). Significantly fewer patients in the RTX group achieved complete remission than the CTX group (14.29% vs. 33.80%, P=0.01). The adverse events rate was similar between the RTX group and the CTX group (28.57% vs. 40.85%, P=0.13). In subgroup analysis, we found that fewer patients from the RTX group achieved the primary endpoint than the CTX group (48.65% vs. 74.29%, P=0.03) among patients with massive proteinuria (urine protein ≥ 8 g/24 h). During the observational phase, 61 patients in the RTX group and 58 in the CTX group completed 24 months of follow-up, exhibiting similar remission rates (RTX vs. CTX: 75.41% vs. 68.97%, P=0.54). Conclusions: Our results show that the intravenous CTX regimen has similar safety and efficacy with higher rates of early complete remission than RTX in the treatment of PMN patients.